Preparation method of Bi / Bi4NbO8X piezoelectric photocatalyst with amorphous crystal interface
By introducing amorphous/crystalline interface into the Bi4NbO8X piezoelectric photocatalyst, combined with the synergistic effect of the LSPR effect of Bi metal and the piezoelectric field, the problem of insufficient performance of the existing Bi4NbO8X piezoelectric photocatalyst is solved, and a significant improvement in catalytic efficiency is achieved and sunlight utilization.
Patent Information
- Application Number
- CN202411596861.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Bi4NbO8X(X=Cl,Br) bismuth-based piezoelectric photocatalysts have problems such as limited piezoelectric photocatalytic performance, low piezoelectric coefficient, fast photoinduced charge recombination, and insufficient sunlight utilization, which affects its effect in practical applications. .
Low-temperature wet chemistry and electrochemical methods are used to prepare Bi/Bi4NbO8X piezoelectric photocatalyst with amorphous/crystalline interface. Through the synergistic effect of Bi metal and the piezoelectric field, the separation and transfer ability of photogenerated carriers is improved.
The degradation reaction rate constant of piezoelectric photocatalysts is significantly improved. Compared with the original Bi4NbO8Cl, the degradation reaction rate constant can reach 11 times, and it shows higher catalytic efficiency under the synergistic action of light and ultrasound.
Smart Images

Figure CN119455988A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Bi / Bi 4 NbO 8 The invention discloses a preparation method of an X-type piezoelectric photocatalyst, and belongs to the technical field of piezoelectric photocatalytic materials. Background Art
[0002] With the acceleration of the process of modern industrialization, the increasingly severe environmental pollution problem has seriously restricted the development of human economic society. In recent years, photocatalytic technology has developed rapidly, which can use sunlight to create renewable and clean energy and degrade environmental pollutants. However, the rapid recombination of photogenerated carriers in the bulk and surface of the catalyst seriously affects the efficiency of photocatalysis. Therefore, it is crucial to develop a technology that simultaneously improves the efficiency of photogenerated charge separation in the bulk and surface of photocatalytic materials.
[0003] In recent years, the use of polarization fields to improve the internal photogenerated carrier separation efficiency has been widely studied. The internal polarization electric field generated by piezoelectric semiconductor materials when subjected to external stress can effectively promote the separation of photogenerated carriers and adjust the band structure of photocatalysts to improve the separation and transfer ability of photogenerated charges. Due to the above attractive properties, piezoelectric semiconductors such as ZnO, NaNbO 3 and BaTiO 3 The piezoelectric photocatalytic activity of catalytic converters has been widely explored, however, their activities are still unsatisfactory.
[0004] Bismuth-based catalysts have a unique layered structure consisting of [Bi 2 O 2 ] layers with interlayer ions or functional groups, which are enriched and low in toxicity. Some of these bismuth-based materials have asymmetric lattices and have piezoelectric properties when subjected to mechanical strain. 4 NbO 8 X(X=Cl,Br) is known for its simplest Sillén-Aurivillius layered perovskite structure, which consists of alternating fluorite [Bi 2 O 2 ], perovskite [NbO 4 ] and halide [Cl / Br] blocks, this layered structure shows great potential as a piezoelectric and photocatalytic material. 4 NbO 8 Bismuth-based piezoelectric photocatalysts such as X (X = Cl, Br) still have problems such as limited piezoelectric photocatalytic performance, low piezoelectric coefficient, rapid photoinduced charge recombination, and insufficient utilization of sunlight, which seriously affect and restrict their practical application.
[0005] Therefore, in order to improve the activity of existing piezoelectric photocatalytic materials, this paper proposes a new piezoelectric photocatalyst with an amorphous / crystalline interface for efficient degradation of tetracycline, as well as its preparation method and application. Summary of the invention
[0006] In order to solve the existing Bi 4 NbO 8 The present invention provides a Bi / Bi photocatalyst having an amorphous / crystalline heterogeneous interface. 4 The preparation method of NbOX piezoelectric photocatalyst, the specific steps are as follows:
[0007] (1)Bi 4 NbO 8 Preparation of X precursor: Add Bi to deionized water 2 O 3 , Nb 2 O 5 , BiOX (X = Cl, Br), NaX (X = Cl, Br), LiX (X = Cl, Br), stir evenly at 0 ° C, calcine the stirred mixture, wash and dry the calcined product to obtain Bi 4 NbO 8 X, wherein X is Cl or Br.
[0008] (2) acBi / Bi 4 Preparation of NbOX: Bi prepared in step (1) 4 NbO 8 The X precursor piezoelectric photocatalyst was dissolved in ethylene glycol solution to obtain an electrolyte, and FTO was used as a working electrode, a graphite rod as a counter electrode, and a saturated calomel electrode as a reference electrode. The deposition was carried out at room temperature under a constant current, and the precipitate was collected, washed, centrifuged, and dried to obtain acBi / Bi 4 NbOX, wherein X is Cl or Br.
[0009] Preferably, in step (1), Bi 2 O 3 , Nb 2 O 5 The molar ratio of BiOX, NaX and LiX is 3:1:2:5:5 to 3:1:2:20:20, wherein X is Cl or Br.
[0010] Preferably, in step (1), BiOX is Bi 2 O 3 and ammonium halide in a ratio of 1:1 and calcined at 300°C, wherein X is Cl or Br, and the ammonium halide is NH 4 Cl or NH 4 Br.
[0011] Preferably, the calcination conditions in step (1) are: calcination at 700°C to 800°C for 16 to 24 hours, the atmosphere is a mixture of nitrogen and hydrogen in any proportion, and the heating rate is 5 min / °C.
[0012] Preferably, in step (2), Bi in ethylene glycol 4 NbO 8 The added amount of the X precursor piezoelectric photocatalyst is 10 mmol / L to 18 mmol / L.
[0013] Preferably, in step (2), the constant current is -5 mA to -20 mA, and the deposition time is 10 to 40 min.
[0014] Beneficial effects of the present invention
[0015] (1) The present invention successfully prepared Bi / Bi with amorphous / crystalline interface 4 NbO 8 X (X = Cl, Br) piezoelectric photocatalyst, the formation of amorphous / crystalline heterointerface provides an excellent transfer channel for electrons, effectively promoting charge separation and transfer.
[0016] (2) The LSPR effect of Bi metal effectively increases the light absorption range, Bi / Bi 4 NbO 8 The formation of X(X=Cl,Br) heterojunction effectively promotes the 4 NbO 8 (X=Cl, Br) The separation of photogenerated carriers generated in the catalytic process, the existence of the piezoelectric field effectively promotes the separation of bulk charges and reduces the Bi 4 NbO 8 The Schottky barrier between the (X=Cl, Br) semiconductor and the Bi metal further promotes the charge transfer between the semiconductor and the metal.
[0017] (3) Experimental verification shows that the present invention helps to inhibit atomic diffusion through low-temperature wet chemical methods, thereby inhibiting the nucleation and growth of crystals. In addition, the electrochemical method successfully precipitates Bi metal and simultaneously induces the formation of an amorphous / crystalline interface, wherein the amorphous / crystalline interface provides an excellent channel for charge transfer, effectively promoting the separation and migration of photogenerated carriers.
[0018] (4) Bi / Bi with amorphous / crystalline interface provided by the method of the present invention 4 NbO 8 The piezoelectric photocatalytic TC degradation reaction rate constant of Cl is the highest that of the original Bi 4 NbO 8In addition, the novel piezoelectric photocatalyst for degrading TC has a significant piezoelectric-photosynergistic effect. The degradation reaction rate constant of TC under the synergistic effect of light and ultrasound is 2.1 times that of light alone and 13.5 times that of piezoelectric alone. It can be seen that the novel piezoelectric photocatalyst with amorphous / crystalline heterogeneous interface provided by the present invention has good application prospects.
[0019] (5) The present invention provides a Bi / Bi 4 NbO 8 The preparation method of the novel piezoelectric photocatalyst with (X=Cl, Br) heterostructure has mild preparation conditions, simple operation and easy large-scale application. The present invention provides a novel piezoelectric photocatalyst with amorphous / crystalline interface Bi / Bi 4 NbO 8 Compared with the original Bi 4 NbO 8 Cl and pure crystalline Bi / Bi 4 NbO 8 Cl has better charge separation and transfer capabilities and higher photogenerated charge utilization, so the piezoelectric photocatalytic performance is significantly improved compared to both BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 For the original Bi 4 NbO 8 The Bi / Bi with amorphous / crystalline heterogeneous interface prepared by the Cl sample and Examples 1 to 4 under different constant current intensity conditions 4 NbO 8 XRD patterns of Cl heterostructure piezoelectric photocatalysts.
[0021] Figure 2 This is the SEM image of the sample prepared in Example 3.
[0022] Figure 3 This is the HRTEM image of the sample prepared in Example 3.
[0023] Figure 4 For the original Bi 4 NbO 8 UV-Vis-IR absorption spectra of the Cl sample and the samples prepared in Examples 1 to 4.
[0024] Figure 5 For the original Bi 4 NbO 8 The Bi / Bi with amorphous / crystalline heterogeneous interface prepared by the Cl sample and Examples 1 to 4 under different constant current intensity conditions 4 NbO 8The degradation of tetracycline by Cl piezoelectric photocatalyst under ultrasound alone, light alone, and ultrasound plus light conditions as well as the reaction rate constant.
[0025] Figure 6 For the original Bi 4 NbO 8 The piezoelectric photocatalytic degradation efficiency of TC by the Cl sample is compared with that of the samples prepared in Comparative Example 1 and Example 3 under the same conditions. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0027] Example 1
[0028] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Cl heterostructure piezoelectric photocatalyst and its preparation method and application:
[0029] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOCl was added to a beaker; 10mmol NaCl and 10mmol LiCl were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace for calcination at 700°C for 24h, with a heating rate of 5°C / min, and an atmosphere of nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Cl precursor piezoelectric photocatalyst, where BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0030] (2) 0.5 mmol of Bi 4 NbO 8 Cl was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. FTO was used as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode. The samples were deposited at -5 mA constant current for 10 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 °C for 12 h to obtain Bi / Bi with an amorphous / crystalline interface. 4 NbO 8 Cl.
[0031] The Bi / Bi with amorphous / crystalline interface prepared in this embodiment 4 NbO 8 The Cl sample was named acBi / BNC-1.
[0032] Example 2
[0033] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Cl heterostructure piezoelectric photocatalyst and its preparation method and application:
[0034] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOCl was added to a beaker; 10mmol NaCl and 10mmol LiCl were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace and calcined at 720°C for 20h, with a heating rate of 5°C / min, and the atmosphere was nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Cl precursor piezoelectric photocatalyst, where BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0035] (2) 0.5 mmol of Bi 4 NbO 8 Cl was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. Using FTO as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode, the samples were deposited at -10 mA constant current for 20 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 ° C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8 Cl.
[0036] The Bi / Bi with amorphous / crystalline interface prepared in this embodiment 4 NbO 8 The Cl sample was named acBi / BNC-2.
[0037] Example 3
[0038] Bi / Bi with amorphous / crystalline heterojunction 4 NbO8 Cl heterostructure piezoelectric photocatalyst and its preparation method and application:
[0039] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOCl was added to a beaker; 10mmol NaCl and 10mmol LiCl were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace and calcined at 750°C for 18h, with a heating rate of 5°C / min, and the atmosphere was nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Cl precursor piezoelectric photocatalyst, where BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0040] (2) 0.5 mmol of Bi 4 NbO 8 Cl was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. Using FTO as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode, the samples were deposited at -15 mA constant current for 30 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 ° C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8 Cl.
[0041] The Bi / Bi with amorphous / crystalline interface prepared in this embodiment 4 NbO 8 The Cl sample was named acBi / BNC-3.
[0042] Example 4
[0043] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Cl heterostructure piezoelectric photocatalyst and its preparation method and application:
[0044] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5, 1mmol BiOCl was added to a beaker; 10mmol NaCl and 10mmol LiCl were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace for calcination at 800°C for 16h, with a heating rate of 5°C / min, and an atmosphere of nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Cl precursor piezoelectric photocatalyst, where BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0045] (2) 0.5 mmol of Bi 4 NbO 8 Cl was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. Using FTO as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode, the samples were deposited at -20 mA constant current for 40 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 ° C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8 Cl.
[0046] The Bi / Bi with amorphous / crystalline interface prepared in this embodiment 4 NbO 8 The Cl sample was named acBi / BNC-4.
[0047] Example 5
[0048] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Br heterostructure piezoelectric photocatalyst and its preparation method and application:
[0049] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOBr was added to a beaker; 2.5mmol NaBr and 2.5mmol LiBr were weighed and added to the beaker, and the mixture was transferred to a corundum crucible after being fully stirred and mixed at 0°C. The mixture was placed in a muffle furnace and calcined at 700°C for 24h with a heating rate of 5°C / min in a nitrogen and hydrogen atmosphere. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8Br precursor piezoelectric photocatalyst, in which BiOBr is composed of Bi 2 O 3 It is prepared by calcining ammonium bromide at 300°C in a 1:1 molar ratio.
[0050] (2) 0.5 mmol of Bi 4 NbO 8 Br was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. FTO was used as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode. The samples were deposited at -5 mA constant current for 10 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 °C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8 Br.
[0051] Example 6
[0052] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Br heterostructure piezoelectric photocatalyst and its preparation method and application:
[0053] Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOBr was added to a beaker; 5mmol NaBr and 5mmol LiBr were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace and calcined at 720°C for 20h, with a heating rate of 5°C / min, and the atmosphere was nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Br precursor piezoelectric photocatalyst, in which BiOBr is composed of Bi 2 O 3 It is prepared by calcining ammonium bromide at 300°C in a 1:1 molar ratio.
[0054] (2) 0.5 mmol of Bi 4 NbO 8 Br was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. FTO was used as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode. The samples were deposited at -10 mA constant current for 20 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 °C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8Br.
[0055] Example 7
[0056] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Br heterostructure piezoelectric photocatalyst and its preparation method and application:
[0057] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOBr was added to a beaker; 10mmol NaBr and 10mmol LiBr were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace and calcined at 750°C for 18h, with a heating rate of 5°C / min, and the atmosphere was nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Br precursor piezoelectric photocatalyst, in which BiOBr is composed of Bi 2 O 3 It is prepared by calcining ammonium bromide at 300°C in a 1:1 molar ratio.
[0058] (2) 0.5 mmol of Bi 4 NbO 8 Br was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. Using FTO as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode, the samples were deposited at -15 mA constant current for 30 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 ° C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8 Br.
[0059] Example 8
[0060] Bi / Bi with amorphous / crystalline heterojunction 4 NbO 8 Br heterostructure piezoelectric photocatalyst and its preparation method and application:
[0061] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5, 1mmol BiOBr was added to a beaker; 10mmol NaBr and 10mmol LiBr were weighed and added to the beaker, and the mixture was fully stirred and mixed at 0°C, and then transferred to a corundum crucible, and placed in a muffle furnace and calcined at 800°C for 16h, with a heating rate of 5°C / min, and the atmosphere was nitrogen and hydrogen. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70°C for 12h to obtain Bi 4 NbO 8 Br precursor piezoelectric photocatalyst, in which BiOBr is composed of Bi 2 O 3 It is prepared by calcining ammonium bromide at 300°C in a 1:1 molar ratio.
[0062] (2) 0.9 mmol of Bi 4 NbO 8 Br was dissolved in 50 ml of ethylene glycol solution to prepare the electrolyte. Using FTO as the working electrode, graphite rod as the counter electrode, and saturated calomel electrode as the reference electrode, the samples were deposited at -20 mA constant current for 40 min at room temperature. The collected samples were washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 ° C for 12 h. Bi / Bi with amorphous / crystalline interface 4 NbO 8 Br.
[0063] Comparative Example 1
[0064] A pure crystalline heterointerface of Bi / Bi 4 NbO 8 Cl heterostructure piezoelectric photocatalyst and its preparation method and application:
[0065] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOCl was added to an agate mortar; 10mmol NaCl and 10mmol KCl were weighed and added to the agate mortar. After sufficient grinding, the mixture was transferred to a corundum crucible and placed in a muffle furnace for calcination at 750℃ for 4h with a heating rate of 5℃ / min in a nitrogen and hydrogen atmosphere. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70℃ for 12h to obtain Bi 4 NbO 8 Cl precursor piezoelectric photocatalyst, where BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0066] (2) Weigh 0.5 mmol of the prepared Bi 4 NbO 8 The Cl precursor material was placed in a crucible, and 90 mmol of PVP (polyvinyl pyrrolidone) was weighed and placed in another crucible. The two were sintered at 500 °C for 2 h in a closed environment, and the resulting pure crystalline Bi / Bi 4 NbO 8 Cl heterojunction material.
[0067] The material prepared in this comparative example is named cBi / BNC, and compared with the material prepared in Example 3, the piezoelectric photocatalytic degradation performance of TC is significantly reduced.
[0068] Comparative Example 2
[0069] A pure crystalline heterointerface of Bi / Bi 4 NbO 8 Cl heterostructure piezoelectric photocatalyst and its preparation method and application:
[0070] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOCl was added to an agate mortar; 10mmol NaCl and 10mmol KCl were weighed and added to the agate mortar. After sufficient grinding, the mixture was transferred to a corundum crucible and placed in a muffle furnace for calcination at 750℃ for 4h with a heating rate of 5℃ / min in a nitrogen and hydrogen atmosphere. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70℃ for 12h to obtain Bi 4 NbO 8 Cl precursor piezoelectric photocatalyst, where BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0071] (2) 0.5 mmol of Bi 4 NbO 8 Cl was dissolved in 50 ml ethylene glycol solution and stirred for 1 h. The sample was transferred to a reactor and hydrothermaled at 160 °C for 6 h. The obtained sample was collected and washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 °C for 12 h. The obtained pure crystalline Bi / Bi 4 NbO 8 Cl heterojunction material.
[0072] The piezoelectric photocatalytic degradation performance of the material prepared in this comparative example is significantly lower than that of the material prepared in Example 3.
[0073] Comparative Example 3
[0074] A pure crystalline Bi / Bi with no amorphous / crystalline heterojunction 4 NbO 8 Br heterostructure piezoelectric photocatalyst and its preparation method and application:
[0075] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5 , 1mmol BiOBr was added to the agate mortar; 10mmol NaBr and 10mmol KBr were weighed and added to the agate mortar. After sufficient grinding, the mixture was transferred to a corundum crucible and placed in a muffle furnace for calcination at 750℃ for 4h with a heating rate of 5℃ / min in a nitrogen and hydrogen atmosphere. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70℃ for 12h to obtain Bi 4 NbO 8 Br precursor piezoelectric photocatalyst, in which BiOCl is composed of Bi 2 O 3 It is prepared by calcining at 300°C with ammonium chloride in a 1:1 molar ratio.
[0076] (2) Weigh 0.5 mmol of the prepared Bi 4 NbO 8 The Cl precursor material was placed in a crucible, and 90 mmol of PVP (polyvinyl pyrrolidone) was weighed and placed in another crucible. The two were sintered at 500 °C for 2 h in a closed environment, and the resulting pure crystalline Bi / Bi 4 NbO 8 Br heterojunction material.
[0077] The piezoelectric photocatalytic degradation performance of the material prepared in this comparative example is significantly lower than that of the material prepared in Example 7.
[0078] Comparative Example 4
[0079] A pure crystalline Bi / Bi with no amorphous / crystalline heterojunction 4 NbO 8 Br heterostructure piezoelectric photocatalyst and its preparation method and application:
[0080] (1) Weigh 1.5 mmol of Bi 2 O 3 , 0.5mmol Nb 2 O 5, 1mmol BiOBr was added to the agate mortar; 10mmol NaBr and 10mmol KBr were weighed and added to the agate mortar. After sufficient grinding, the mixture was transferred to a corundum crucible and placed in a muffle furnace for calcination at 750℃ for 4h with a heating rate of 5℃ / min in a nitrogen and hydrogen atmosphere. The calcined sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70℃ for 12h to obtain Bi 4 NbO 8 Br precursor piezoelectric photocatalyst, in which BiOBr is composed of Bi 2 O 3 It is prepared by calcining ammonium bromide at 300°C in a 1:1 molar ratio.
[0081] (2) 0.5 mmol of Bi 4 NbO 8 Br was dissolved in 50 ml of ethylene glycol solution and stirred for 1 h. The sample was transferred to a reactor and hydrothermaled at 160 °C for 6 h. The collected sample was washed with deionized water and anhydrous ethanol, centrifuged, and dried at 70 °C for 12 h.
[0082] The piezoelectric photocatalytic degradation performance of the material prepared in this comparative example is significantly lower than that of the material prepared in Example 7.
[0083] Performance Testing
[0084] For the original Bi 4 NbO 8 The materials prepared by Cl(BNC) and Examples 1 to 4 were subjected to relevant performance tests. First, the prepared materials were subjected to X-ray diffraction analysis. The results are as follows: Figure 1 As shown in the figure, it can be seen that with the increase of current intensity and time, the crystallinity of the sample gradually decreases, and the formation of amorphous / crystalline interface gradually increases.
[0085] The material prepared in Example 3 was subjected to SEM and TEM analysis, and the results were as follows: Figure 2 and Figure 3 As shown, it can be clearly observed that Bi 4 NbO 8 There is the loading of Bi metal particles and the formation of amorphous / crystalline interface on the surface of Cl nanosheets.
[0086] For the original Bi 4 NbO 8 The Cl(BNC) sample and the materials prepared in Examples 1 to 4 were subjected to absorption spectrum tests. The results are as follows: Figure 4 As shown, with the increase of amorphous / crystalline heterointerfaces, the light absorption ability of the sample gradually increases.
[0087] For the original Bi4 NbO 8 The Cl(BNC) sample and the materials prepared in Examples 1 to 4 and Comparative Example 1 were tested for the piezoelectric photocatalytic degradation of tetracycline. The results are as follows: Figure 5 and Figure 6 As shown in the figure, the formation of amorphous / crystalline interface effectively improves the piezoelectric photocatalytic performance of the material. The piezoelectric photocatalytic tetracycline degradation efficiency of the sample acBi / BNC-3 prepared in Example 3 is 2.3 times that of the original Bi 4 NbO 8 Cl sample, and the piezoelectric photocatalytic performance of the cBi / BNC sample prepared in Comparative Example 1 was significantly enhanced.
Claims
1. A method for preparing a Bi / Bi4NbO8X piezoelectric photocatalyst having an amorphous crystalline interface, characterized in that: The specific steps are as follows: (1) Preparation of Bi4NbO8X precursor: Add Bi2O3, Nb2O5, BiOX, NaX, and LiX into deionized water, stir evenly at 0°C, calcine the stirred mixture, wash and dry the calcined product to obtain Bi4NbO8X, wherein X is Cl or Br; (2) Preparation of acBi / Bi4NbOX: The Bi4NbO8X precursor piezoelectric photocatalyst prepared in step (1) is dissolved in an ethylene glycol solution to obtain an electrolyte, and FTO is used as a working electrode, a graphite rod is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode. Deposition is performed at room temperature under a constant current, and the precipitate is collected, washed, centrifuged, and dried to obtain acBi / Bi4NbOX, wherein X is Cl or Br.
2. The method for preparing the Bi / Bi4NbO8X piezoelectric photocatalyst having an amorphous crystal interface according to claim 1, characterized in that: In step (1), the molar ratio of Bi2O3, Nb2O5, BiOX, NaX and LiX is 3:1:2:5:5 to 3:1:2:20:20, wherein X is Cl or Br.
3. The method for preparing the Bi / Bi4NbO8X piezoelectric photocatalyst having an amorphous crystal interface according to claim 1, characterized in that: In step (1), BiOX is prepared by calcining Bi2O3 and ammonium halide at a molar ratio of 1:1 at 300°C, wherein X is Cl or Br, and the ammonium halide is NH4Cl or NH4Br.
4. The method for preparing the Bi / Bi4NbO8X piezoelectric photocatalyst having an amorphous crystal interface according to claim 1, characterized in that: The calcination conditions in step (1) are: calcination at 700°C to 800°C for 16 to 24 hours, an atmosphere of nitrogen and hydrogen mixed in any proportion, and a heating rate of 5 min / °C.
5. The method for preparing the Bi / Bi4NbO8X piezoelectric photocatalyst having an amorphous-crystallization interface according to claim 1, characterized in that: In step (2), the amount of Bi4NbO8X precursor piezoelectric photocatalyst added to ethylene glycol is 10 mmol / L to 18 mmol / L.
6. The method for preparing the Bi / Bi4NbO8X piezoelectric photocatalyst having an amorphous-crystallization interface according to claim 1, characterized in that: In step (2), the constant current is -5 mA to -20 mA, and the deposition time is 10 to 40 minutes.
Citation Information
Patent Citations
Preparation method of Bi-supported Bi4NbO8Cl composite visible light catalyst
CN110694650A
Preparation method of Bi4NbO8Cl
CN110773205A
Cited By
Piezoelectric coupling photocatalyst as well as preparation method and application thereof
CN120790190A
Cu-S-Bi4NbO8Br photocatalyst as well as preparation method and application thereof
CN121534747A